Efektivitas Pengelolaan QRIS pada Pengguna Baru Bale by BTN Mobile di Bank BTN KCP Ketintang Surabaya - Lidya Dwi Nur Afiqoh; Lia Nirawati (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to evaluate the QRIS management program for new users of Bale by BTN Mobile at Bank BTN KCP Ketintang, especially in the distribution of Surabaya University student identification cards and customer service. The method applied is descriptive qualitative with data collection through interviews, in-depth observations, and documentation. There are four informant subjects related to this research, namely new customers, business people, customer service, and funding parties of Bank BTN KCP Ketintang, selected to obtain an in-depth understanding of the effectiveness of the program. The results showed an increase in the use of QRIS among new users of Bale by BTN. Through the cashback program, customers can use QRIS regularly. However, the use of technology and online systems in this program still faces challenges, especially related to technical problems that often arise in Bale by BTN mobile banking, which can hinder the smooth activation process.